PENGARUH PENDIDIKAN KESEHATAN TERHADAP PENINGKATAN PENGETAHUAN HIV PADA REMAJA DI SMP ADVENT SURAKARTA - Kristiana Puji Purwandari (Akademi Keperawatan Giri Satria Husada Wonogiri, 2020)
HIV is a virus where the virus aims to attack the human immune system causing weakness in the body to fight a disease. HIV stands for Human Immunodeficiency Virus, when interpreted in Indonesian it means a virus that can cause a decrease in human immunity. HIV is a virus in which the virus can attack the immune system. This study aims to determine the comparison of the level of knowledge before and after treatment in the form of health education regarding the prevention of HIV transmission.Measurements were carried out twice, through a questionnaire given before the provision of health education (pre test) and a questionnaire after the provision of health education (post test) which was used to measure differences in knowledge levels after an intervention in the form of health education for prevention of HIV transmission. This study used a quantitative quasi-experimental method using a one- group pre-test-post-test research design. This type of research design